Heat fluctuations in Ising models coupled with two different heat baths - Piscitelli, Antonio (2015)
Monte Carlo simulations of Ising models coupled to heat baths at two different temperatures are used to study a fluctuation relation for the heat exchanged between the two thermostats in a time τ. Different kinetics (single-spin-flip or spin-exchange Kawasaki dynamics), transition rates (Glauber or Metropolis), and couplings between the system and the thermostats have been considered. In every case the fluctuation relation is verified in the large τ limit, both in the disordered and in the low temperature phase. Finite-τ corrections are shown to obey a scaling behavior.